Myopia in elementary school students in Eastern China during the COVID-19 pandemic - Huang, Shuaishuai; Shen, Fanhan; Zhou, Fujun; Gong, Qinghai; Liu, Kui; Feng, Wei; Cen, Dong (Frontiers in Public Health, 2023)
Background: Myopia is an increasingly serious public concern, particularly among primary school students. The aim of this study was to explore myopia prevalence in primary school pupils in Eastern China during the COVID-19 pandemic, to examine the potential influencing factors, with a view to implementing measures to prevent and control myopia in this special group. Methods: Fifteen primary schools in the Fenghua District of Zhejiang Province were randomly selected for inclusion in 2020 and then students without myopia from 135 classes from grade 1 to grade 3 were selected. All included students were given myopia screening and completed uniform questionnaire survey one year later. Results: A total of 4,387 respondents met the inclusion criteria, of which 4,213 (96.03%) completed the myopia screening and questionnaire survey. The spherical equivalent (SE) refraction of the 4,213 pupils decreased on average by 0.50 ± 2.15 D one year later. Myopia was diagnosed in 1,356 pupils, with a myopia rate of 32.19%. The myopia rate was positively correlated with the increase of grade, in which the myopia rate among grade 3 students was the highest at 39.69%. The myopia rate among female students was higher than that among male students. Students residing in urban areas had a higher myopia rate than in rural areas. Maintaining an near work distance >33 cm was a significant protective factor (odds ratio [OR]=0.84, 95% confidence interval [CI]=0.74–0.96). Students with two myopic parents had a higher rate of myopia (OR=1.61, 95% CI=1.34–1.92). Conclusion: During the COVID-19 pandemic, the myopia rate among early primary school students in Eastern China was high. More attention and implementation of interventions from health and education departments, such as training the development of good eye behavior, should be considered to strengthen the intervention of myopia in primary school students.